2018
DOI: 10.3390/lubricants6040102
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of CO2 Emissions and Cost Analysis of Ultra-Low Viscosity Engine Oil

Abstract: This study is focused on the reduction of CO2 emissions and costs associated with ultra-low viscosity (ULV) engine oils for passenger vehicles. Specifically, the reduction in life cycle CO2 (LCCO2) emissions from lower-viscosity engine oil and the oil drain interval (ODI) extension were estimated taking into account both mineral engine oil and synthetic engine oil. Furthermore, the cost-effectiveness of ULV engine oils were investigated by performing base-stock cost analysis. When the volatility limit of the N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 20 publications
(33 reference statements)
0
4
0
Order By: Relevance
“…The advent of electric vehicles means that thermally activated lubricant additives are less effective, and it also presents new requirements for lubricants, such as extremely low viscosity at speeds higher than 20,000 rpm [1], placing greater demands on the boundary-lubrication performance upon startup. Internal combustion and hybrid vehicles will be with us for decades yet, and among the measures proposed for energy saving [2] have been self-healing ultrathin tribofilms that are active under boundary-lubrication conditions in reduced-viscosity lubricants [3]. Wind turbines have rapidly ascended in importance, but their effective lubrication, including under boundary-lubrication conditions, remains a significant challenge [4].…”
Section: Introductionmentioning
confidence: 99%
“…The advent of electric vehicles means that thermally activated lubricant additives are less effective, and it also presents new requirements for lubricants, such as extremely low viscosity at speeds higher than 20,000 rpm [1], placing greater demands on the boundary-lubrication performance upon startup. Internal combustion and hybrid vehicles will be with us for decades yet, and among the measures proposed for energy saving [2] have been self-healing ultrathin tribofilms that are active under boundary-lubrication conditions in reduced-viscosity lubricants [3]. Wind turbines have rapidly ascended in importance, but their effective lubrication, including under boundary-lubrication conditions, remains a significant challenge [4].…”
Section: Introductionmentioning
confidence: 99%
“…The global task of the energy efficiency and saving within the context of the machine's exploitation will require the consideration of both viscosity reduction and oil drain interval extension [5]. Minimization of the environmental pollution should also be taken into account [4].…”
Section: Discussionmentioning
confidence: 99%
“…Low-viscosity engine oils, transmission and hydraulic fluids have the potential to substantially increase the energy performance of machines and mechanisms [1][2][3][4][5]. The development of new synthetic approaches to novel types of oils and lubricants with leading characteristics is a relevant task of applied chemistry [6].…”
Section: Introductionmentioning
confidence: 99%
“…Ishizaki and Nakano [10] have reported that, for lubricants made from mineral base oils, approximately 1 kg of CO 2 is emitted for each litre of lubricant manufactured, of which 0. comes from the additives contained within the lubricant. For the more commonly used synthetic lubricants used in most modern passenger cars, it was estimated that 1.65 kg of CO 2 was emitted per litre of lubricant manufactured (with around 0.25 kg of this figure coming from the additives).…”
Section: The Co 2 Impact Of Lubricationmentioning
confidence: 99%